Efficacy of strains of Metarhizium anisopliae (Metsch) Sorokin with their different preparations against white grub (Chiloloba acuta) in vitro in Nepal - Khanal, Dipak; GC, Yubak D; Giri, Yagya P; Sporleder, Marc; Thapa, Resham B (Journal of Agriculture and Environment, 2014)
Laboratory studies were conducted to evaluate the virulence of an indigenous and a commercial strain of the entomopathogenic fungi, Metarhiziuma nisopliae (Metsch.) Sorokin in three different preparations against third instars larva of Chiloloba acuta.Conidia of the indigenous strain were multiplied on barley grain, ("Ind-G") while the commercial strain was tested in its powder ("Com-P") and solution ("Com-S") preparations. All fungus preparations were bioassayed at different concentrations levels; i.e. "Ind-G" at 60, 10, 1.66, 0.27, 0.046 g/ kg of soil, "Com-P" at 10, 1.66, 0.27, 0.046, 0.0077g/kg of soil and "Com-S" at 10, 1.66, 0.27, 0.046, 0.0077g /(100 ml water+ 1 kg soil). The LC50-value of Ind-G (0.41 g/kg of soil) was higher as compared to Com-P (0.11 g/kg of soil) and Com-S (0.10 g/kg of soil) revealing relative potencies of 1, 3.27 (CL 95% ranging 1.01- 10.29) and 4.11(CL 95% ranging 1.28 to13.01), respectively at 40 days after inoculation (DAI). Based on this study there is great possibility that the entomopathogenic fungi could be a safe microbial control agents in managing white grubs.